A single crystal ternary positive electrode material and its preparation method and application

By using single crystal core-shell structure design and gradient doping technology in ternary positive electrode materials, a stable cladding layer and fast ion conductive layer are formed, which solves the problem of poor cycling performance and gas production performance at high voltage, and achieves high energy density and excellent kinetic performance.

CN114243014BActive Publication Date: 2025-03-25GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111276497.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-29
Publication Date
2025-03-25
Estimated Expiration
2041-10-29

AI Technical Summary

Technical Problem

The existing ternary positive electrode materials have poor cycling and gas production performance at high voltages, and the content of doped elements is too high, resulting in a low capacity.

Method used

The core-shell structure design of a single crystal ternary positive electrode material is used, and a stable structure is formed through lattice doping and surface gradient doping, and then coated and low-temperature tempered to form a cladding layer with a low residual lithium content on the surface and a fast ion conductive layer.

Benefits of technology

It achieves stable structure, high energy density, excellent cycling and kinetic performance under high voltage conditions, reduces the interface side reaction between the material and the electrolyte, and improves the cycling and gas production performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114243014B_ABST
    Figure CN114243014B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion batteries and discloses a single crystal ternary positive electrode material and a preparation method and application thereof. The chemical formula of the single crystal ternary positive electrode material is LiNi x Co y Mn z M (1‑x‑y‑z) O c @Li a N d O b , 0<x≤0.65, 0<y≤0.15, 0<z≤0.35, 0<a≤6, 0<b≤4, 1<c≤2, 1≤d<2; M and N are at least one of Zr, Ni, Al, Cu, Co, Sr, Mn, Y, Ti, Mg, Mo, B, Sn, Fe, Zn, Si or W. The single crystal ternary positive electrode material of the present invention is a single crystal material with a core-shell structure, low residual lithium on the surface, stable internal and external structures, high energy density, and excellent cycle performance and kinetic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a single-crystal ternary positive electrode material and a preparation method and application thereof. Background Art

[0002] Ternary cathode materials have always attracted attention from the new energy industry due to their high specific capacity, high specific energy density, good cycle, safety and low cost. In general, in order to obtain higher capacity, the research and development directions of ternary materials are mainly divided into the following two directions: the first direction is to increase the nickel content and prepare high-nickel materials, but Li and Ni have similar radii, and the exchange of Ni and Li leads to lithium-nickel mixing. The greater the concentration of nickel ions in the lithium layer, the more difficult it is for lithium to be deintercalated in the layered structure, the worse the stability of the material, the worse the safety, and the higher the cost; the second direction is to increase the charge and discharge voltage of the material, so that the lithium in the lattice of the ternary material can be more removed and inserted, resulting in structural instability of the material, and the surface side reactions of the cathode material and the electrolyte under high voltage are aggravated, consuming lattice lithium and hindering the transmission of lithium, resulting in deterioration of the material cycle and serious gas production.

[0003] At present, the circulation and gas production problems of materials under high voltage are mainly solved by improving the stability of the material substrate, reducing the surface area of ​​the material, and isolating the direct contact between the material and the electrolyte. The main treatment method is to dope to improve the safety and stability of the material itself, mainly to support the structure of the columnar material when more lithium is removed. The doping is mainly the doping of zirconium, titanium, aluminum, tungsten, magnesium, scandium, vanadium, calcium, strontium, barium, gallium, indium and other elements. The coating of a stable coating layer and increasing the size of the single crystal particles reduce the contact reaction between the material and the electrolyte and the metal dissolution effect, thereby reducing the gas production and circulation problems of the battery cell. Generally, the coating uses metal oxides (Al2O3, TiO2, ZnO, ZrO2, etc.) to modify the surface of the ternary material. However, under high voltage, in order to maintain the stable structure of the material, the content of the doping element is a bit high. Excessive doping will make the material structure stable, but the capacity of the material will be a bit low. Material coating and large particles will cause the DCR of the material to increase, especially when the discharge potential is low. It is difficult for lithium ions in the electrolyte to enter the lattice of the positive electrode material, resulting in low material capacity and poor cycle performance. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a single crystal ternary positive electrode material and a preparation method and application thereof, wherein the single crystal ternary positive electrode material has a stable structure, high capacity, and excellent cycle performance and kinetic performance.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A single crystal ternary cathode material with the chemical formula LiNi x Co y Mn z M (1-x-y-z) O c @Li a N d O b , wherein 0<x≤0.65, 0<y≤0.15, 0<z≤0.35, 0<a≤6, 0<b≤4, 1<c≤2, 1≤d<2; M is at least one of Zr, Ni, Al, Cu, Co, Sr, Mn, Y, Ti, Mg, Mo, B, Sn, Fe, Zn, Si or W; N is at least one of Zr, Ni, Al, Cu, Co, Sr, Mn, Y, Ti, Mg, Mo, B, Sn, Fe, Zn, Si or W.

[0007] Preferably, the chemical formula of the single crystal ternary cathode material is LiNi 0.596 Co 0.05 Mn 0.35 M 0.004 O c @Li2N d O4; the M is at least one of Zr, Zn, Si or W; the N is at least one of Zr, Al, Mo, Zn, Si or W, wherein x=0.596, y=0.05, z=0.35, a=2, b=4, 1<c≤2, 1≤d<2.

[0008] More preferably, M is Zr and W.

[0009] More preferably, N is Zr, Al and W.

[0010] Preferably, the particle size of the single crystal ternary positive electrode material is 1.0-5.0 μm, and the particle specific surface area is 0.4-0.8 m 2 / g.

[0011] A method for preparing a single crystal ternary cathode material comprises the following steps:

[0012] (1) mixing nickel salt, manganese salt and cobalt salt, adding a precipitant and a complexing agent, reacting, and separating the solid and the liquid to obtain a precursor;

[0013] (2) mixing the precursor with a lithium source and a dopant, performing a first sintering, and crushing to obtain a single crystal material;

[0014] (3) The single crystal material and the second dopant are mixed, and sintered for a second time. A coating agent is then added and mixed, and sintered for a third time to obtain a single crystal positive electrode material.

[0015] The above-mentioned single crystal ternary cathode material is a ternary cathode material with stable structure, high energy density, excellent cycle performance and kinetic performance under high voltage conditions. By doping the single crystal lattice to improve the internal structural stability, and then gradient doping the surface of the single crystal material at high temperature, a single crystal material with stable structure from the inside to the surface and no micropowder is constructed. Finally, after coating and low-temperature tempering, a coating layer and a fast ion conductive layer with low residual lithium content on the surface are formed, which can supplement the lithium source lost during the battery cycle. The fast ion conductive network is formed by lattice doping, surface gradient doping of materials, less micropowder, lithium supplement and crystal surface. The electrochemical performance of the cathode material under high voltage is improved under the joint action of these strategies.

[0016] Preferably, in step (1), the nickel salt is at least one of nickel sulfate, nickel chloride and nickel nitrate.

[0017] Preferably, in step (1), the manganese salt is at least one of manganese sulfate, manganese chloride and manganese nitrate.

[0018] Preferably, in step (1), the cobalt salt is at least one of cobalt sulfate, cobalt chloride and cobalt nitrate.

[0019] Preferably, in step (1), the precipitant is sodium hydroxide.

[0020] Preferably, in step (1), the complexing agent is aqueous ammonia.

[0021] Preferably, in step (1), the reaction temperature is 60-90° C., and the reaction time is 70-75 h.

[0022] Preferably, in step (1), the pH is maintained at 9.5-12.0 during the reaction.

[0023] Preferably, in step (1), after the solid-liquid separation, the solid phase is further dried; the drying temperature is 100-125° C. and the drying time is 24-30 hours.

[0024] Preferably, in step (1), the particle size distribution D50 of the precursor is 3.8-4.5 μm.

[0025] Preferably, in step (1), the stirring speed during the reaction is 500-600 r / min.

[0026] Preferably, in step (2), the lithium source is at least one of LiOH, Li2CO3, LiNO3 or CH3COOLi.

[0027] Preferably, in step (2), the molar ratio of lithium in the lithium source to the metal element in the precursor is 1:(1.06-1.25).

[0028] Preferably, in step (2), the dopant 1 is an oxide of at least one of the following doping elements: Zr, Ni, Al, Cu, Co, Sr, Mn, Y, Ti, Mg, Mo, B, Sn, Fe, Zn, Si or W; and the total content of the doping elements is 300-5000 ppm.

[0029] Further preferably, the dopant one is at least one of ZrO2, NiO, Al2O3, CuO, CoO, Co3O4, SrO, MnO2, Y2O3, TiO2, MgO, MoO2, B2O3, SnO2, Fe2O3, ZnO, SiO2 or WO3.

[0030] Preferably, in step (2), the mixing speed is 300-500 r / min, and the mixing time is 0.5-1.5 h.

[0031] Preferably, in step (2), the first sintering process is: introducing air / oxygen at a pressure of 0.15-0.5Mpa, raising the temperature to 450-800°C at a heating rate of 0.5-5.0°C / min for pre-sintering for 3-8h, continuing to heat to 850°C-950°C at the same heating rate for sintering, keeping warm for 8-15h, and naturally cooling to room temperature.

[0032] After the first sintering, a polycrystalline granular material with doped elements in the lattice and more residual lithium between the lattices is obtained.

[0033] Preferably, in step (2), the pulverizing process is: the pulverizing process is: performing pulverizing by rotary mill and air flow mill in sequence. Further, the rotary mill is used to pulverize the material to be pulverized into a particle size of 1-2 mm.

[0034] Preferably, in step (3), the dopant 1 is an oxide of at least one of the following doping elements: Zr, Ni, Al, Cu, Co, Sr, Mn, Y, Ti, Mg, Mo, B, Sn, Fe, Zn, Si or W; and the total content of the doping elements is 1000-10000 ppm.

[0035] Further preferably, the second dopant is at least one of ZrO2, NiO, Al2O3, CuO, CoO, Co3O4, SrO, MnO2, Y2O3, TiO2, MgO, MoO2, B2O3, SnO2, Fe2O3, ZnO, SiO2 or WO3.

[0036] After the second sintering, a surface gradient doping is formed on the surface of the single crystal.

[0037] Preferably, in step (3), the second sintering process is: introducing air / oxygen at a pressure of 0.15-0.5Mpa, raising the temperature to 650-950°C at a heating rate of 0.5-5.0°C / min for pre-sintering for 3-8h, and cooling naturally to room temperature.

[0038] Preferably, in step (3), the coating agent is an oxide of at least one of the following coating elements: Zr, Ni, Al, Cu, Co, Sr, Mn, Y, Ti, Mg, Mo, B, Sn, Fe, Zn, Si or W; and the total content of the coating element is 1000-5000 ppm.

[0039] Further preferably, the coating agent is at least one of ZrO2, NiO, Al2O3, CuO, CoO, Co3O4, SrO, MnO2, Y2O3, TiO2, MgO, MoO2, B2O3, SnO2, Fe2O3, ZnO, SiO2 or WO3.

[0040] Preferably, in step (3), the third sintering process is: introducing air / oxygen at a pressure of 0.15-0.5Mpa, raising the temperature to 450-650°C at a heating rate of 0.5-5.0°C / min for pre-sintering for 1-6h, and cooling naturally to room temperature.

[0041] A battery comprises the single crystal ternary positive electrode material.

[0042] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0043] 1. The single crystal ternary cathode material LiNi of the present invention x Co y Mn z M (1-x-y-z) O2@Li a NO b It is a single crystal material with a core-shell structure, low residual lithium on the surface, stable internal and external structure, high energy density, excellent cycle performance and kinetic performance. It is first doped to form a fast ion conductor, and then the surface is gradient doped and coated to form a coating layer and fast ion conductive layer with low residual lithium content on the surface, which can replenish the lithium source lost during the battery cycle, thereby improving the electrochemical performance of the positive electrode material under high voltage.

[0044] 2. The present invention uses the first sintering to make the lithium source react with the dopant to form a fast ion conductor, improve the electronic and ion transmission channels of the material, reduce the local overpotential and affect the stability of the material structure, and improve the ion and electron transmission kinetics of the material. The second sintering forms a surface gradient doping (a structurally stable coating layer) on the surface of the single crystal. The crystal structure of this coating layer is close to the internal structure. Even if the thickness of the prepared shell is very small, the volume will not expand or shrink during the charge and discharge process to cause the surface layer of the material to fall off, so as to achieve a stable surface of the single crystal. In addition, the high temperature will also react the micropowder generated in the process of breaking into a single crystal sample with the lithium source remaining on the surface to form a positive electrode material, reduce the BET and residual lithium of the material, reduce the side reactions on the surface of the material in the battery, and improve the battery's cycle performance, gas production performance and impedance growth.

[0045] 3. During the third sintering of the present invention, the residual lithium source on the surface of the single crystal material reacts with some elements (elements of the coating agent) to form a lithium replenisher that replenishes the loss of lattice lithium during the charge and discharge process. Especially in the case of deep delithiation caused by high voltage, the excess residual lithium on the surface of the material is converted into a favorable lithium replenisher or fast ion channel, which will significantly improve the cycle performance and rate performance of the single crystal material in the battery.

[0046] 4. In the process of preparing single crystal materials, the present invention reduces the mixing of lithium and nickel elements in the material by increasing the molar ratio of lithium to precursor metal elements, thereby obtaining a single crystal ternary material with integrity of the internal structure; in addition, other elements are doped into the lattice to stabilize the crystal structure inside the material. The high molar ratio of lithium to precursor metal elements will have unreacted lithium sources, which will become favorable fast ion conductors and lithium supplements, thereby improving the rate and cycle performance of the material. In addition, the stable core-shell structure forms a stable structure for the interior and surface of the material on the basis of ensuring the capacity, thereby improving the BET (specific surface area) and residual lithium of the material, reducing the occurrence of interface side reactions between the material and the electrolyte in the battery, thereby improving the cycle and gas production performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 Phase XRD diagrams of single crystal positive electrode materials prepared in Example 1 and Comparative Example 1;

[0048] Figure 2 The phase SEM image of the single crystal positive electrode material prepared in Example 1;

[0049] Figure 3 This is a SEM image of the positive electrode material prepared in Comparative Example 2;

[0050] Figure 4 This is a SEM image of the positive electrode material prepared in Comparative Example 3;

[0051] Figure 5The cycling performance diagram of the single crystal ternary positive electrode material prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3. DETAILED DESCRIPTION

[0052] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0053] Example 1

[0054] The single crystal ternary positive electrode material of this embodiment has a chemical formula of LiNi 0.596 Co 0.05 Mn 0.35 M 0.004 O2@Li2NO4; M is Zr and W; N is Zr, Al and W; the average particle size of the single crystal particles is 1.5-3μm and the specific surface area is 0.4-0.8cm 2 / g.

[0055] The preparation method of the single crystal ternary positive electrode material of this embodiment has the following specific steps:

[0056] (1) NiSO4, CoSO4, and MnSO4 were prepared into a mixed solution with a total metal ion concentration of 1.6 mol / L according to a Ni:Co:Mn molar ratio of 0.60:0.05:0.35, and then a 10 mol / L NaOH solution was prepared;

[0057] (2) The mixed solution was introduced into a reactor, and then the NaOH solution and the ammonia solution were introduced into the reactor and stirred for 70 hours. The reaction temperature was adjusted to 70° C., the stirring speed was 500 r / min, and the pH in the reactor was maintained at 9.5-12.0. After filtering and washing with water, vacuum drying was performed at 120° C. for 24 hours to obtain a lamellar porous precursor with a particle size distribution of D50=3.8-4.5 μm;

[0058] (3) 3 kg of the precursor was mixed with lithium carbonate, ZrO2 and WO2 (the metal molar ratio of lithium to precursor in lithium carbonate was 1.15, and the total content of Zr and W was 4000 ppm), and the first sintering was carried out under air conditions of 0.2 MPa, with a heating rate of 3 ° C / min, and the temperature was raised to 750 ° C, and the temperature was kept for 5 hours. The temperature was further raised to 950 ° C for sintering and the temperature was kept for 12 hours. The cooling procedure was to cool to room temperature with the furnace, and then crushed and passed through a 300 mesh sieve to obtain a single crystal ternary positive electrode material with low lithium-nickel mixing and stable structure;

[0059] (4) The crushed single crystal ternary cathode material was mixed with ZrO2 (Zr content was 2000ppm), and a second sintering was performed under air conditions of 0.2MPa, with a heating rate of 3°C / min from room temperature to 750°C, and the temperature was kept for 4h, and then cooled to room temperature to obtain a single crystal material with a surface gradient doped with metal;

[0060] (5) The single crystal material after the second sintering is mixed with Al2O3 and WO3 (the total content of Al and W is 4000ppm), and sintered for the third time under air conditions of 0.2MPa at a heating rate of 3℃ / min, raised to 450℃, kept at this temperature for 5h, and cooled to room temperature to obtain a single crystal ternary positive electrode material.

[0061] The XRD analysis of the phase of the single crystal ternary cathode material in this embodiment is as follows: Figure 1 As shown, the appearance is Figure 2 shown; from Figure 2 It can be seen that after the third sintering, a uniform coating layer is formed on the surface of the single crystal.

[0062] Through the above steps, a ternary single crystal positive electrode material is obtained which has a stable structure, a high capacity, and excellent cycle performance and kinetic performance under high voltage conditions.

[0063] The positive electrode material, conductive agent SP and binder PVDF were mixed in a ratio of 8:1:1 (total mass 20g) and added to 20g of NMP organic solvent solution to obtain a mixed solution. The mixed solution was stirred to obtain a slurry, which was evenly coated on an 8μm aluminum foil with a thickness of 200μm, and dried in a vacuum drying oven at 120°C for 4h. The dried electrode was compacted on a 30T roller press and finally cut into circular positive electrode sheets with a diameter of 14mm. The mass of active material in the circular sheet was approximately 15.00g. The cut positive electrode sheets, electrolyte and separator were assembled into button batteries. The electrochemical properties of the battery were tested after resting. The test reference current density was 1C=190mA / g.

[0064] Example 2

[0065] The single crystal ternary positive electrode material of this embodiment has a chemical formula of LiNi 0.799 Co 0.1 Mn 0.1 M 0.001 O2@Li2NO4; M is Zr and W; N is Zr, Al and W; the average particle size of the single crystal particles is 1.5-3μm and the specific surface area is 0.4-0.8cm 2 / g.

[0066] The preparation method of the single crystal ternary positive electrode material of this embodiment has the following specific steps:

[0067] (1) NiSO4, CoSO4, and MnSO4 were prepared into a mixed solution with a total metal ion concentration of 1.6 mol / L according to a Ni:Co:Mn molar ratio of 0.80:0.10:0.10, and then a 10 mol / L NaOH solution was prepared;

[0068] (2) The mixed solution was introduced into a reactor, and then the NaOH solution and the ammonia solution were introduced into the reactor and stirred for 70 hours. The reaction temperature was adjusted to 70° C., the stirring speed was 500 r / min, and the pH in the reactor was maintained at 10. After filtering and washing with water, vacuum drying was performed at 120° C. for 24 hours to obtain a lamellar porous precursor with a particle size distribution of D50=3.8-4.5 μm;

[0069] (3) 3 kg of the precursor was mixed with lithium carbonate, ZrO2 and WO2 (the metal molar ratio of lithium to precursor in lithium carbonate was 1.15, and the total content of Zr and W was 4000 ppm), and the first sintering was carried out under air conditions of 0.2 MPa, with a heating rate of 3 ° C / min, and the temperature was raised to 750 ° C, and the temperature was kept for 5 hours. The temperature was further raised to 950 ° C for sintering and the temperature was kept for 12 hours. The cooling procedure was to cool to room temperature with the furnace, and then crushed and passed through a 300 mesh sieve to obtain a single crystal ternary positive electrode material with low lithium-nickel mixing and stable structure;

[0070] (4) The crushed single crystal ternary cathode material was mixed with ZrO2 (Zr content was 2000ppm), and a second sintering was performed under air conditions of 0.2MPa, with a heating rate of 3°C / min from room temperature to 750°C, and the temperature was kept for 4h, and then cooled to room temperature to obtain a single crystal material with a surface gradient doped with metal;

[0071] (5) The single crystal material after the second sintering is mixed with Al2O3 and WO3 (the total content of Al and W is 4000ppm), and sintered for the third time under air conditions of 0.2MPa at a heating rate of 3℃ / min, raised to 450℃, kept at this temperature for 5h, and cooled to room temperature to obtain a single crystal ternary positive electrode material.

[0072] Through the above steps, a ternary single crystal positive electrode material is obtained which has a stable structure, a high capacity, and excellent cycle performance and kinetic performance under high voltage conditions.

[0073] The positive electrode material, conductive agent SP and binder PVDF were mixed in a ratio of 8:1:1 (total mass 20g) and added to 20g of NMP organic solvent solution to obtain a mixed solution. The mixed solution was stirred to obtain a slurry, which was evenly coated on an 8μm aluminum foil with a thickness of 200μm, and dried in a vacuum drying oven at 120°C for 4h. The dried electrode was compacted on a 30T roller press and finally cut into circular positive electrode sheets with a diameter of 14mm. The mass of active material in the circular sheet was approximately 15.00g. The cut positive electrode sheets, electrolyte and separator were assembled into button batteries. The electrochemical properties of the battery were tested after resting. The test reference current density was 1C=190mA / g.

[0074] Comparative Example 1

[0075] The specific steps of the preparation method of the single crystal ternary positive electrode material of this comparative example are as follows: The steps of comparative example 1 are almost the same as those of example 1, except that the lithium addition in step (3) of the example is changed to 1.05.

[0076] The XRD pattern of the positive electrode material obtained by the method of Comparative Example 1 is as follows: Figure 1 shown.

[0077] Comparative Example 2

[0078] The specific steps of the preparation method of the single crystal ternary positive electrode material of this comparative example are as follows: The material preparation of comparative example 2 is almost the same as that of example 1, except that step (4) of the embodiment is removed.

[0079] The morphology of the positive electrode material obtained by the method of comparative example 2 is as follows Figure 3 shown.

[0080] Comparative Example 3

[0081] The preparation method of a single crystal ternary positive electrode material in this comparative example has the following specific steps: The material preparation of comparative example 3 is almost the same as that of example 1, except that step (5) of the embodiment is removed.

[0082] The morphology of the positive electrode material obtained by the method of comparative example 3 is as follows Figure 4 shown.

[0083] Comparative Example 4

[0084] The preparation method of a single crystal ternary positive electrode material in this comparative example has the following specific steps: ZrO2, Al2O3, and WO3 in steps 4 and 5 remain unchanged, and only the two processes are implemented through a one-step doping process in step 4.

[0085] Comparative Example 5

[0086] The preparation method of a single crystal ternary positive electrode material in this comparative example has the following specific steps: ZrO2, Al2O3, and WO3 in steps 4 and 5 remain unchanged, and only the two processes are implemented through a one-step coating process in step 5.

[0087] Analysis of Example 1 and Comparative Examples 1-3:

[0088] Figure 1 The XRD data of Example 1 and Comparative Example 1 show that the (006) / (102) and (108) / (110) crystal plane peaks are clearly separated, indicating that both materials have high crystallinity. In addition, the (003) / (104) crystal plane peak intensity ratio in XRD is greater than 1.2, indicating that both materials have good layered crystal structures and small lithium-nickel mixing. The peak intensity and (003) / (104) peak ratio of Example 1 in XRD are stronger than those of Comparative Example 1, indicating that the crystallinity of the material of Example 1 is better and the degree of lithium-nickel mixing is lower. At the same time, the peak position of Example 1 is to the left of the peak position of Comparative Example 1, indicating that the interlayer spacing of the material is larger. The above results show that relatively high lithium coordination improves the structural integrity of the material and the interlayer spacing of the material, indicating that it is more favorable for the escape and entry of lithium ions, and the reason for the improved lithium ion utilization rate and large diffusion coefficient is that it has a great influence on the kinetics of the material. Figure 2 The single crystal ternary positive electrode material prepared in Example 1 has a protective layer on the surface of the material. The protective layer consumes residual lithium on the surface and fine powder generated by the pulverization process during the formation process, which is beneficial to improving the gas production of the battery. Secondly, the protective layer can supplement the loss caused by the lithium side reaction in the lattice under high voltage. Thirdly, the protective layer can isolate the side reaction between the electrolyte and the positive electrode material of the battery. Therefore, the above protective layer can significantly improve the cycle performance and capacity of the material. Figure 3 This is the SEM image of the single crystal ternary cathode material prepared in Comparative Example 2. There are a lot of fine powders on the surface of the material due to crushing; Figure 4 This is a SEM image of the single crystal ternary cathode material prepared in Comparative Example 3. The material is doped on the surface at high temperature, and the surface of the formed material is relatively smooth, with less fine powder, and residual lithium is clearly seen on the surface of the material; Figure 5 The cycle performance of the materials prepared in Example 1 and Comparative Examples 1-3 is shown. It can be clearly seen from the surface of the materials that the material prepared in Example 1 has better cycle performance and the highest capacity. The first cycle test results of the button half-cell positive electrode materials in Example 1 and Comparative Examples 1-3 are shown in Table 1.

[0089] Table 1 Data of Example 1 and Comparative Examples 1-3

[0090]

[0091] Table 1 is a comparison of the electrochemical properties of the positive electrode materials of Example 1 and Comparative Examples 1-3. Example 1 has a maximum voltage of 4.45V, a 0.1C first discharge specific capacity of 194.7mAh / g, and a discharge efficiency of 89.2%, which is significantly higher than the specific capacity and efficiency of the positive electrode material of the comparative example. By adding more lithium, the lithium-nickel mixing and lattice spacing of the material are significantly improved, and the crystal structure of the ternary material is stabilized by doping. In addition, a more stable shell is constructed by doping the surface layer to protect the structural stability of the internal material. At the same time, the coating converts the unfavorable residual lithium on the surface of the single crystal material into a favorable fast ion conductive network or lithium supplement. In summary, the energy barrier for lithium ion escape and embedding is reduced, thereby improving the first-cycle specific capacity and efficiency of the material.

[0092] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A single crystal ternary cathode material, characterized in that: The chemical formula of the single crystal ternary cathode material is LiNi x Co y Mn z M (1-x-y-z) O c @Li a N d O b , wherein 0<x≤0.65, 0<y≤0.15, 0<z≤0.35, 0<a≤6, 0<b≤4, 1<c≤2, 1≤d<2; M is at least two of Zr, Ni, Al, Cu, Co, Sr, Mn, Y, Ti, Mg, Mo, B, Sn, Fe, Zn, Si or W; N is at least two of Zr, Ni, Al, Cu, Co, Sr, Mn, Y, Ti, Mg, Mo, B, Sn, Fe, Zn, Si or W; The method for preparing the single crystal ternary cathode material comprises the following steps: (1) mixing nickel salt, manganese salt and cobalt salt, adding a precipitant and a complexing agent, reacting, separating the solid and the liquid, and taking the solid phase to obtain a precursor; (2) mixing the precursor with a lithium source and a dopant, performing a first sintering, and crushing to obtain a single crystal material; (3) The single crystal material and the second dopant are mixed, and sintered for a second time. A coating agent is then added and mixed, and sintered for a third time to obtain a single crystal positive electrode material.

2. The single crystal ternary cathode material according to claim 1, characterized in that: The chemical formula of the single crystal ternary positive electrode material is LiNi 0.596 Co 0.05 Mn 0.35 M 0.004 O c @Li2NdO4; the M is at least two of Zr, Zn, Si or W; the N is at least two of Zr, Al, Mo, Zn, Si or W, wherein x=0.596, y=0.05, z=0.35, a=2, b=4, 1<c≤2, 1≤d<2.

3. The method for preparing the single crystal ternary cathode material according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) mixing nickel salt, manganese salt and cobalt salt, adding a precipitant and a complexing agent, reacting, separating the solid and the liquid, and taking the solid phase to obtain a precursor; (2) mixing the precursor with a lithium source and a dopant, performing a first sintering, and crushing to obtain a single crystal material; (3) The single crystal material and the second dopant are mixed, and sintered for a second time. A coating agent is then added and mixed, and sintered for a third time to obtain a single crystal positive electrode material.

4. The preparation method according to claim 3, characterized in that: In step (1), the nickel salt is at least one of nickel sulfate, nickel chloride, and nickel nitrate; the manganese salt is at least one of manganese sulfate, manganese chloride, and manganese nitrate; and the cobalt salt is at least one of cobalt sulfate, cobalt chloride, and cobalt nitrate.

5. The preparation method according to claim 3, characterized in that: In step (2), the lithium source is at least one of LiOH, Li2CO3, LiNO3 or CH3COOLi.

6. The preparation method according to claim 3, characterized in that: In step (2), the molar ratio of lithium in the lithium source to the total molar ratio of nickel, cobalt and manganese in the precursor is 1:(1.06-1.25).

7. The preparation method according to claim 3, characterized in that: In step (2), the dopant 1 is an oxide of at least one of the following doping elements: Zr, Ni, Al, Cu, Co, Sr, Mn, Y, Ti, Mg, Mo, B, Sn, Fe, Zn, Si or W; and the total content of the doping elements is 300-5000 ppm.

8. The preparation method according to claim 3, characterized in that: In step (3), the second dopant is an oxide of at least one of the following doping elements: Zr, Ni, Al, Cu, Co, Sr, Mn, Y, Ti, Mg, Mo, B, Sn, Fe, Zn, Si or W; the total content of the doping element is 1000-10000 ppm; in step (3), the coating agent is an oxide of at least one of the following coating elements: Zr, Ni, Al, Cu, Co, Sr, Mn, Y, Ti, Mg, Mo, B, Sn, Fe, Zn, Si or W; the total content of the coating element is 1000-5000 ppm.

9. The preparation method according to claim 3, characterized in that: In step (3), the second sintering process is as follows: introducing air / oxygen at a pressure of 0.15-0.5Mpa, raising the temperature to 650-950°C at a heating rate of 0.5-5.0°C / min, performing pre-sintering for 3-8h, and naturally cooling to room temperature.

10. A battery, characterized in that: It comprises the single crystal ternary positive electrode material as described in any one of claims 1-2.

Citation Information

Patent Citations

  • Ternary positive electrode material and preparation method thereof, lithium ion battery and electric vehicle

    CN110867573A

  • High-nickel ternary positive electrode material and preparation method thereof

    CN112103496A